Impact of somatic mutations on prognosis in resected non‐small‐cell lung cancer: The Japan Molecular Epidemiology for lung cancer study. (5th February 2020) - Tamiya, Akihiro; Koh, Yasuhiro; Isa, Shun‐ichi; Kubo, Akihito; Ando, Masahiko; Saka, Hideo; Yoshimoto, Naoki; Takeo, Sadanori; Adachi, Hirofumi; Tagawa, Tsutomu; Kawashima, Osamu; Yamashita, Motohiro; et al.
Abstract: Background: To report the follow up data and clinical outcomes of the JME study (UMIN 000008177), a prospective, multicenter, molecular epidemiology examination of 876 surgically resected non‐small‐cell lung cancer (NSCLC) cases, and the impact of somatic mutations (72 cancer‐associated genes) on recurrence‐free survival (RFS) and overall survival (OS). Methods: Patients were enrolled between July 2012 and December 2013, with follow up to 30th November 2017. A Cox proportional hazards model was used to assess the impact of gene mutations on RFS and OS, considering sex, smoking history, age, stage, histology, EGFR, KRAS, TP53, and number of coexisting mutations. Results: Of 876 patients, 172 had ≥2 somatic mutations. Median follow‐up was 48.4 months. On multivariate analysis, number of coexisting mutations (≥2 vs 0 or 1, HR = 2.012, 95% CI: 1.488‐2.695), age (≥70 vs <70 years, HR = 1.583, 95% CI: 1.229‐2.049), gender (male vs female, HR = 1.503, 95% CI: 1.045‐2.170) and pathological stage (II vs I, HR = 3.386, 95% CI: 2.447‐4.646; ≥III vs I, HR = 6.307, 95% CI: 4.680‐8.476) were significantly associated with RFS, while EGFR mutation (yes vs no, HR = 0.482, 95% CI: 0.309‐0.736), number of coexisting mutations (≥2 vs 0 or 1, HR = 1.695, 95% CI: 1.143‐2.467), age (≥70 vs <70 years, HR = 1.932, 95% CI: 1.385‐2.726), and pathological stage (II vs I, HR = 2.209, 95% CI: 1.431‐3.347; ≥III vs I, HR = 5.286, 95% CI: 3.682‐7.566) were also significant for OS. Conclusion: A smaller number of coexisting mutations, earlier stage, and younger age were associated with longer RFS and OS, while EGFR mutations were significantly associated with improved OS. Abstract : A prospective, multi‐center, molecular epidemiology study of 876 surgically resected non‐small cell lung cancer cases, and the impact of somatic mutations (72 cancer‐associated genes) on recurrence‐free survival and overall survival (OS). A smaller number of co‐existing mutations, earlier stage, and younger age were associated with longer recurrence free survival and OS, while epidermal growth factor receptor mutations were significantly associated with improved OS.